The rough guide to India 2024 - Edwards, Nick; Edwards, Maria; Narayan, Rashmi; Sahu, Supriya (Rough Guides, 2024)
"This practical travel guide to India features detailed factual travel tips and points-of-interest structured lists of all iconic must-see sights as well as some off-the-beaten-track treasures. Our itinerary suggestions and expert author picks of things to see and do will make it a perfect companion both, ahead of your trip and on the ground. This India guide book is packed full of details on how to get there and around, pre-departure information and top time-saving tips, including a visual list of things not to miss. Our colour-coded maps make India easier to navigate while you're there." --